'Don't follow them, look at me!': Contemplating a haptic digital prototype to bridge the conductor and visually impaired performer. (27th May 2019) - Baker, David; Fomukong-Boden, Ann; Edwards, Sian
ABSTRACT: This paper reports on an exploratory research-and-development project concerning a device for conveying a conductor's gestures wirelessly to a visually impaired (blind or partially sighted) performer as a haptic signal. The research team developed this device from January to July 2017 under a University College London (UCL) Institute of Education 'seed-corn' grant. As a platform for its development, they firstly observed and analysed video footage of conductors at the Royal Academy of Music, London using Elan software to create a gestural model. Subsequently, through gaining blind end-users' feedback on the device, as well as an experiment to compare their timing using either (i) a two-dimension haptic signal or (ii) a metronomic pulsation, it is suggested that the development of technologies for this purpose should focus on the meaning the conductor intends to convey coupled with haptic signals blind end-users themselves deem suitable, rather than adopting a 'sighted perspective' in attempting faithful transference of two-dimensional captures of arm movements from one medium to another. Reasons for this assertion are explored.